Contralateral selectivity of upper limb motor pools via targeted stimulation of the cervical spinal cord. - Fleming, Neil; Reilly, Richard (My University, 2023)
Transcutaneous spinal cord stimulation (tSCS) at the cervical level may facilitate improved upper-limb function in those with incomplete tetraplegia. While clinical trials are ongoing, there is still much debate regarding the transmission pathway as well as appropriate stimulation parameters. This study aimed to explore the extent to which cervical tSCS can induce mono-synaptic reflexes in discrete upper-limb motor pools and examine the effects of altering stimulus location and intensity. Methods: Fourteen participants with intact nervous systems completed two laboratory visits, during which posterior root-muscle reflexes (PRMRs) were evoked via a 3 × 3 cathode matrix applied over the cervical spine. An incremental recruitment curve at the C7 vertebral level was initially performed to attain resting motor threshold (RMT) in each muscle. Paired pulses (1 ms square monophasic with inter-pulse interval of 50 ms) were subsequently delivered at a frequency of 0.25 Hz at two intensities (RMT and RMT + 20%) across all nine cathode positions. Evoked responses to the 1st (PRMR1) and 2nd (PRMR2) stimuli were recorded in four upper-limb muscles. Results: A significant effect of the spinal level was observed in all muscles for PRMR1, with greater responses being recorded caudally. Contralateral stimulation significantly increased PRMR1 in Biceps Brachii (p < 0.05, F = 4.9, η2 = 0.29), Flexor Carpi Radialis (p < 0.05, F = 4.9, η2 = 0.28) and Abductor Pollicis Brevis (p < 0.01, F = 8.9, η2 = 0.89). Post-activation depression (PAD) was also significantly increased with contralateral stimulation in Biceps Brachii (p = 0.001, F = 9.3, η2 = 0.44), Triceps Brachii (p < 0.05, F = 5.4, η2 = 0.31) and Flexor Carpi Radialis (p < 0.001, F = 17.4, η2 = 0.59). Conclusions: A level of unilateral motor pool selectivity may be attained by altering stimulus intensity and location during cervical tSCS. Optimising these parameters may improve the efficacy of this neuromodulation method in clinical cohorts.
PUBLISHED
Keywords: Cervical spine; Spinal cord injury; tSCS; Transcutaneous spinal cord stimulation; Upper limb; Neuroscience; MOTONEURON POOLS; NEUROMODULATION; Mobility impairment; Physical disability; Sensory impairment